IMPROVING STUDENTS’ VOCABULARY MASTERY USING SPELLING BEE GAME AT FIFTH GRADE IN SDIT YA BUNAYYA PUJON - Martha Prasetya Ningrum; Indrawati Pusparini (UIBU, 2020)
This research caused by lacking of students’ vocabulary mastery in English Subject. One of the methods to improve vocabulary is Spelling Bee game. This action research aims to measure the use of spelling bee game to improve student’s mastery in English vocabulary and to determine student’s responses motivated towards the application of spelling bee game. The research uses classroom action research (CAR) caused by Arikunto Suharsimi at students’ fifth grade in SDIT Ya Bunayya Pujon. The research is done in two cycle. In every cycle consist of three meeting with the activity: planning, action, observation and reflection. Pre-test and post-test are given in the form of vocabulary tests. Data obtained from the pre-test and post-test were analysis in a classical completeness with a minimum quality standard of 75. The results of the analysis show that in cycle 1 was an average score of 70.26 with a classical completeness of 47, 05%. Furthermore, the results of the study in cycle 2 getting a significant improvement in which the score obtained was an average of 82.91 with a classical completeness reaching 88.24%. An increase from cycle 1 to cycle 2 in the classical completeness obtained reaching 41.19%. While, the implementation of the method makes students pay more attention, more active, and motivated in learning English. From these results it means that the application of the game Spelling Bee has an influence on improving students' mastery of English vocabulary. Finally, from this study, we can conclude that this application is recommended to teachers to create a pleasant atmosphere for students, especially young learner in learning English vocabulary.